PROBIOTIC CANDIDATE PROTEOLYTIC Bacillus sp. COLLECTED FROM MANGROVE OF MARGASARI, LAMPUNG - Sumardi Sumardi; Komang Rima; Salman Farisi; Endang Linirin Widiastuti (Indonesian Journal of Forestry Research, 2021)
Intensive shrimp culture has encountered many problems, such as declining water quality through disease caused by pathogenic microbes, which affected mortality. This study aimed to determine any potential probiotic from Bacillus sp. collected from mangrove in East Lampung, which could be used to improve the cultured shrimps' proteolytic and probiotic activity. This is a descriptive research with sampling and data collection of bacteria from many samples of mangrove. Result shows 128 isolates Bacillus from which then it has arrived at five potential probiotic Bacillus sp. The study five Bacillus sp. has been isolated with potential properties for probiotic (KPP212, IP121, UJ131, UJ132, SB141). Each isolate has characteristics with proteolytic property, growth in a wide range of pH 4–10 and osmotic stress (0–6% NaCl), non-pathogenic, ability for glucose fermentation, non-motile, and has negative catalase activity. The five potential Bacillus sp. can be used as probiotics for shrimp farming.